Interplay between sarcopenia, GDF-15, and the efficacy of nivolumab plus ipilimumab in patients with mismatch repair deficient metastatic colorectal cancer: final survival analysis of the phase II GERCOR NIPICOL study - Christelle de La Fouchardière; Jaafar Bennouna; David Tougeron; Thierry André; Christophe Tournigand; Christophe Borg; Romain Cohen; Thibault Mazard; Dewi Vernerey; Frédéric Pigneur; Julie Henriques; Aurélia Meurisse; et al. (Journal for ImmunoTherapy of Cancer)
Background Sarcopenia and growth differentiation factor 15 (GDF-15) are linked to poor cancer survival. In this exploratory analysis, we evaluated their interaction with nivolumab-ipilimumab efficacy in chemoresistant metastatic colorectal cancer (mCRC) harboring microsatellite instability and/or mismatch-repair deficiency (MSI/dMMR), based on the final survival analysis of the NIPICOL phase II trial.Patients and methods 57 patients with MSI/dMMR chemoresistant mCRC received nivolumab-ipilimumab for 3 months (3M), then, nivolumab alone for 9M. Skeletal muscle mass index (SMI) was evaluated by CT scan at baseline and 12M to assess sarcopenia. GDF-15 levels were assessed at baseline and 3M. Main endpoints were overall survival (OS) and immune Response Evaluation Criteria In Solid Tumors progression-free survival (iPFS).Results After excluding three patients not confirmed as MSI/dMMR by central review, the overall median follow-up was 60.4 months. The 3-year and 5 year iPFS rates were 72.0% and 65.3%, with OS rates of 77.5% and 73.3%, respectively. Among 49 patients with evaluable GDF-15, high-baseline GDF-15 was associated with poorer survival: 3-year iPFS rate of 56.3% for GDF-15≥2500 versus 81.7% for GDF-15<2500 (PFS HR=2.45, 95% CI 0.91 to 6.55), 3-year OS rates of 61.4% versus 84.5% (OS HR=2.08, 95% CI 0.70 to 6.22). Of the 48 evaluable patients for SMI, 31 (65.0%) displayed sarcopenia at baseline. 11 out of 20 (55%) patients with baseline sarcopenia and assessed for SMI at 12M, reversed sarcopenia by 12M. They had higher baseline GDF-15 levels and greater GDF-15 decrease by 3M (delta mean change: −69.8% vs −40.3%) compared with patients who remained sarcopenic.Conclusion 1-year nivolumab-ipilimumab demonstrates consistent efficacy after 5-year follow-up in an MSI/dMMR chemoresistant mCRC population. GDF-15 confirms to be a promising biomarker for sarcopenia and survival.Trial registration number NCT03350126.